MUC1 attenuates neutrophilic airway inflammation in asthma by reducing NLRP3 inflammasome-mediated pyroptosis through the inhibition of the TLR4/MyD88/NF-κB pathway - Lu Liu; Ling Zhou; Lingling Wang; Zhenyu Mao; Pengdou Zheng; Fengqin Zhang; Huojun Zhang; Huiguo Liu (Respiratory Research, 2023)
Abstract Background Neutrophilic airway inflammation is a challenge in asthma management and is associated with poor patient prognosis. Mucin 1 (MUC1), which contains a cytoplasmic tail (MUC1-CT), has been found to mediate glucocorticoid sensitivity in asthma; however, its role in modulating neutrophilic airway inflammation in asthma remains unknown. Methods Human-induced sputum cells were collected from healthy participants (n = 12), patients with mild-to-moderate asthma (n = 34), and those with severe asthma (n = 18). In vitro human lung bronchial 1 epithelial cell line (BEAS-2B) was transfected with small interfering RNA against MUC1 (MUC1-siRNA) and then stimulated by lipopolysaccharide (LPS), where some cells were pretreated with a TLR4 inhibitor (TAK-242). In vivo mouse model of asthmatic neutrophil airway inflammation was induced by ovalbumin (OVA)/LPS. Some groups were intraperitoneally injected with MUC1-CT inhibitor (GO-203) and/or TAK-242 . Results The mRNA expression of MUC1 was downregulated in the induced sputum of patients with asthma and correlated with asthmatic neutrophilic airway inflammation. The mRNA expressions of TLR4, MyD88, nucleotide-binding oligomerization domain-like pyrin domain-containing protein 3 (NLRP3), caspase-1, interleukin (IL)-18, and IL-1β in induced sputum cells of patients with asthma were upregulated and related to the mRNA expression of MUC1. LPS activated the TLR4 pathway and NLRP3-mediated pyroptosis in BEAS-2B cells in vitro, which were significantly aggravated after MUC1-siRNA transfection. Furthermore, MUCl-CT interacted with TLR4, and the interaction between TLR4 and MyD88 was significantly increased after MUCl-siRNA transfection. Moreover, TAK-242 ameliorated TLR4/MyD88/nuclear factor kappa B (NF-κB) pathway activation, NLRP3 inflammasome-mediated pyroptosis, and neutrophilic inflammation exacerbated by MUC1 downregulation. GO-203 exacerbated TLR4/MyD88/NF-κB pathway activation in vivo, and NLRP3 inflammasome-mediated pyroptosis reduced in a mouse model of asthmatic neutrophil airway inflammation induced by OVA/LPS; these pathological changes were partially alleviated after TAK-242 application. Conclusion This study revealed that MUC1 downregulation plays an important role in asthmatic neutrophilic airway inflammation. MUC1-CT reduces NLRP3 inflammasome-mediated pyroptosis by inhibiting the activation of the TLR4/MyD88/NF-κB pathway, thereby attenuating neutrophil airway inflammation in patients with asthma.